METODE PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PERUBAHAN LINGKUNGAN PADA SISWA KELAS X SMAN 1 SUNGKAI SELATAN TP 2019/2020 - Riyanti, Tina (Lentera: Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study is to increase the activity and learning outcomes of Environmental Change through the Problem Based Learning (PBL) method. The research was carried out at SMA Negeri 1 Sungkai Selatan Sungkai Selatan, North Lampung in class X semester I students for the 2019/2020 academic year. The research method used in this research is Classroom Action which is carried out through three cycles within a period of three months. The subjects of this study were students of Class X SMA Negeri 1 Sungkai Selatan. The results showed that the Problem Based Learning (PBL) learning model could increase the activity and learning outcomes of Environmental Change students in class X SMA Negeri 1 Sungkai Selatan.